2018
DOI: 10.1002/2211-5463.12415
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolomics and glycolysis enzyme profiling of embryogenic and nonembryogenic grape cells

Abstract: A novel biological model was created for the comparison of grapevine embryogenic cells ( EC ) and nonembryogenic cells ( NEC ) sharing a common genetic background but distinct phenotypes, when cultured on their respective most appropriate media. Cytological characterization, 1 H‐ NMR analysis of intracellular metabolites, and glycolytic enzyme activities provided evidence for the marked metabolic differences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 63 publications
0
11
0
1
Order By: Relevance
“…The IDPs have been described as highly dynamic and conformational heterogeneous structures showing a propensity to undergo induced partial folding upon binding to a partner or under constraint non-physiological conditions [52][53][54]. The disordered nature of the four above-mentioned ASRs highlights structural similarities between ASR and LEA, and corroborates the classification of ASR proteins as a subfamily of the LEAPs superfamily [22,49,55,56]. A hypothesis, whose veracity has yet to be tested, predicts many LEAPs as positively associated with stress memory in Arabidopsis [57].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The IDPs have been described as highly dynamic and conformational heterogeneous structures showing a propensity to undergo induced partial folding upon binding to a partner or under constraint non-physiological conditions [52][53][54]. The disordered nature of the four above-mentioned ASRs highlights structural similarities between ASR and LEA, and corroborates the classification of ASR proteins as a subfamily of the LEAPs superfamily [22,49,55,56]. A hypothesis, whose veracity has yet to be tested, predicts many LEAPs as positively associated with stress memory in Arabidopsis [57].…”
Section: Discussionmentioning
confidence: 67%
“…The latter corroborates the idea that the repression of grape ASR affects plant metabolism, and this in the absence of apparent phenotypic alterations (Figure 1B,C). In this regard, we have already reported that 41B embryogenic cells cope with the low level of intracellular glucose and the low glycolysis efficiency still capable of sustaining their organized cell proliferation [49]. Furthermore, genetically modified plantlets, regenerated from transgenic somatic embryos, did not display apparent phenotypic differences when compared to those of the wild-type plantlets cultured under the same heterotrophic conditions (Figure S1).…”
Section: Discussionmentioning
confidence: 75%
“…Taking advantage of our recent demonstration of the differences in the glycolytic metabolism of embryogenic and non-embryogenic grape cells [ 71 ], we decided to study the positioning of the VvMSA/ VvHT1 interaction in the different pathways of the glucose signaling. The analysis of grape ASR gene expression in embryogenic and non-embryogenic cells clearly confirmed the overexpression and the silencing of VvMSA gene compared to the wild type, and thus allowed us to compare six cellular models.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we explored the biological functions of grape ASR, VvMSA, through its overexpression or repression in genetically transformed grape cell lines of both types, embryogenic (EC) and non-embryogenic (NEC). As previously described by us, the embryogenic cells have been characterized by organized cell proliferation, low intracellular glucose content and low glycolysis flux, while the non-embryogenic cells displayed anarchic cell proliferation, supported by high glucose content and high glycolysis flux [ 71 ]. In these well-characterized cell cultures, we deciphered VvMSA positioning as a transcriptional regulator of the glucose transporter gene VvHT1 in glucose signaling, using different glucose analogs to discriminate between distinct pathways of glucose signal transduction.…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Heringer et al (2015) dan Oliveira et al (2017), kalus embriogenik memiliki warna lebih pekat atau doff, dan tidak translusen seperti pada kalus non-embriogenik karena sel-sel kalus embriogenik mengandung akumulasi protein dan karbohidrat yang lebih tinggi dibandingkan kalus non-embriogenik. Secara fungsional, Passamani et al (2018) dan Parrilla et al (2018) menjelaskan bahwa kalus embriogenik memiliki aktivitas metabolisme yang tinggi, seperti pertukaran ion H + sel, tahap awal glikolisis, fosforilasi oksidatif, sehingga memiliki kapasitas regenerasi embrio somatik yang tinggi apabila diinduksi melalui embriogenesis somatik. Maka pada penelitian ini, selanjutnya kalus embriogenik yang diperoleh digunakan sebagai bahan propagasi massal kurma klonal melalui embriogenesis somatik, yang meliputi tahap induksi embrio somatik, perkecambahan embrio somatik, dan pembentukan planlet.…”
Section: Inisiasi Kalus Embriogenik Kurmaunclassified